Lithuanian Population’s Attitude Towards Vaccines - Petraitytė, Evelina; Skučienė, Daiva (Socialinė teorija, empirija, politika ir praktika, 2026)
Attitudes towards vaccination and the choice of information sources about vaccination are important factors related to public perceptions of vaccines. The aim of this study was to analyse the attitudes of residents of the Republic of Lithuania towards vaccination according to sociodemographic characteristics. The study used data from Eurobarometer 91.2, including only Lithuanian respondents (N = 1004). Binary and multinomial nominal logistic regression were applied for data analysis. The findings showed that attitudes towards vaccination and the choice of information sources differed significantly by age, type of place of residence, gender, and, in some cases, employment status. The findings showed that the most pronounced differences were related to the type of place of residence: rural residents were more likely than residents of large cities to agree with negative statements about vaccination. In contrast, differences between age groups were not consistent across all analyses, and therefore the attitudes of younger respondents should be interpreted with caution.